A national scale big data analytics pipeline to assess the potential impacts of flooding on critical infrastructures and communities. (November 2020) - Donratanapat, N.; Samadi, S.; Vidal, J.M.; Sadeghi Tabas, S.
Abstract: With the rapid development of the Internet of Things (IoT) and Big Data infrastructure, crowdsourcing techniques have emerged to facilitate data processing and problem solving particularly for flood emergences purposes. A Flood Analytics Information System (FAIS) has been developed as a Python Web application to gather Big Data from multiple servers and analyze flooding impacts during historical and real-time events. The application is smartly designed to integrate crowd intelligence, machine learning (ML), and natural language processing of tweets to provide flood warning with the aim to improve situational awareness for flood risk management. FAIS, a national scale prototype, combines flood peak rates and river level information with geotagged tweets to identify a dynamic set of at-risk locations to flooding. The prototype was successfully tested in real-time during Hurricane Dorian flooding as well as for historical event (Hurricanes Florence) across the Carolinas, USA where the storm made extensive disruption to infrastructure and communities. Highlights: FAIS is a national scale Big data gathering and engineering pipeline. The pipeline integrates crowd intelligence and machine learning to identify a dynamic set of at-risk areas to flooding. FAIS tested operationally during Hurricane Dorian Flooding in the Carolinas.